2023
DOI: 10.4081/aiua.2023.11100
|View full text |Cite
|
Sign up to set email alerts
|

Semen and sex-steroid parameters among inflammatory bowel disease ulcerative colitis type according to rectal bleeding grade

Abstract: Introduction: Hypogonadism and inflammato-ry bowel disease (IBD) are often associated. This association may influence sexual and reproductive function in IBD, including sperm profile and sex steroid hormones. Patients and methods: This study included 59 IBD patients diag-nosed with ulcerative colitis type IBD. Anamnesis was carried out regarding the history of the disease, along with a history of rectal bleeding. Evaluation proceeded with sperm and hormone examination if the patient agreed.Results: Progressive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 8 Our previous research demonstrated that the degree of rectal bleeding in IBD had a significant impact on testosterone and free testosterone levels. 1 The study also found a significant correlation of semen parameters, particularly progressive motility, immotile spermatozoa, and normal spermatozoa morphology with the degree of rectal bleeding in IBD. 1 Grosen et al .…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“… 8 Our previous research demonstrated that the degree of rectal bleeding in IBD had a significant impact on testosterone and free testosterone levels. 1 The study also found a significant correlation of semen parameters, particularly progressive motility, immotile spermatozoa, and normal spermatozoa morphology with the degree of rectal bleeding in IBD. 1 Grosen et al .…”
Section: Introductionmentioning
confidence: 66%
“…IBD is caused by factors such as the immune system, environmental factors, gut flora, and genetics. 1 2 3 IBD is divided into two subtypes: ulcerative colitis (UC) and Crohn’s disease (CD). The incidence of CD is approximately 2.1–6 per 100 000 people, while UC is seen in 2.2–4.5 per 100 000 people.…”
Section: Introductionmentioning
confidence: 99%
“…However, this correlation was not observed in UC patients. In male patients with UC, there exists an inverse correlation between testosterone levels and the severity of rectal bleeding ( 12 ). Furthermore, male patients with CD exhibit lower serum testosterone levels compared to healthy individuals ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…For UC, in male patients in remission, there are no significant differences in serum levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), and total testosterone (TT) compared to healthy men ( 11 ). However, studies have indicated a negative correlation between testosterone levels and the extent of rectal bleeding in male UC patients ( 12 ). For CD, in male patients, serum levels of testosterone, estradiol (E2) and sex hormone binding globulin (SHBG) are lower than those in healthy individuals ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a reduction in testosterone levels may have a certain impact on the occurrence and development of chronic diseases. Observational studies have demonstrated a negative correlation between the severity of IBD and sex hormones and semen quality (7) in male patients. Changes in human serum testosterone levels are associated with a variety of diseases, including COVID- 19 (8, 9), nonalcoholic fatty liver disease (9), cardiovascular disease (10), chronic obstructive pulmonary disease (11) and IBD (12).…”
Section: Introductionmentioning
confidence: 99%